Income Smoothing - an Analysis on the Current Evidence of Research - Ramli, Sohimi (1999)
In writing this paper I have one aim; that is to produce a descriptive research paper. It will have clear objectives 1 . I tried to follow as much as possible the recommended research formae . The format is arranged to achieve the objectives and to provide continuos flow of information. I set a high standard for myself. I strived to follow as fully as possible the criteria set for a full master thesis; even though this study is actually only a three months project work. The criteria for any PhD and a full master thesis can be defined as: (an) original contribution to learning which is coherently structured and clearly presented and which shows evidence of systematic study and of ability to relate the results of such study to the general body of knowledge in the subject. A such I think this study is pertinent because it fits particularly well especially to the last part of the criteria. In due course of my study I found there is a glaring lacked of research being done in the Asian region context. Data are difficult to come by. In the end I relied more on Western based research database. Asian region operate under unique business and accounting environment. They represent different story altogether. Knowledge culled from the western experience might not necessarily be congruent. Therefore if academics and practitioners want to understand the Asian perspectives, more research in this region must be promoted. In the end only two Singapore study; which have some relevance on income smoothing; were used in this paper. They provided invaluable knowledge to local researchers in local universities. The dearth of research might stem from lacked of proper recording of local data and insufficient expertise .